Intrapersonal and extrinsic factors to career advancement of female academicians - Hassan, Abubakar Idris; Baharom, Mohd Nazri; Abdul Mutalib, Rozita (2016)
Female participation in the formal sector is steadily increasing in both male and female-oriented organizations around the world. However, the proportion of women entry to top positions of management is relatively low compared to the number of the able female labour force in the Nigeria.Therefore, the study examines the intrapersonal and extrinsic factors of career advancement of female academicians in Nigerian universities. The study adopted the qualitative approach and interviewed seven female staff that had received career progression.The data collected was analyzed through NVivo 10 and found that individual, organizational and societal factors were potential factors to career advancement. Thus, this is an insight that individual, organizational and societal factors are viable predictors to the career advancement of female academic staff. Recommendation for the future study was given in the study.